Tecnologia e inovação social na governança participativa: maior utilização de ferramentas da tecnologia da informação e comunicação como apoio na participação social no Conselho Estadual de Promoção de Igualdade Racial de Minas Gerais - Nayara de Castro Dias (2021)
This qualitative case study aimed to analyze the greater use of Communication and Information Technology (ICT) tools, from 2019 to 2021, in a social participation council, hereby referred to as Minas Gerais State Council for Racial Equality Promotion (CONEPIR). Furthermore, on how managerial changes with the greater use of these ICT tools in participatory governance result in changes in participation and social innovations. This study also addresses the bottlenecks of this dynamic, taking into account the paradigms both in the convergence of the use of technological tools and social participation of the public considered, as well as the innovation in first-sector environments. For this last item is given focus on social innovation in this scenario studied. Data collection was done through study of institutional documents, minutes and semi-structured interviews with seven (07) CONEPIR’s members. For this last approach, a focus on social innovation in the studied scenario is provided. As result, it is found that the performance of the collegiate with the use of ICT tools is impacted by social innovation, and also by the state capacity. That is, even if there is openness and efforts by the public of this collegiate to make greater use of these Information and Communication Technology tools, as well as openness to social innovation, it appears that better management in some elements that are fundamental in the process of participatory governance in this council are still points that must be developed by Public Management. And it is concluded that the social innovation in the processes of participation in CONEPIR was a response of the members of the collegiate facing the need to use ICT tools determined top down for the collegiate in the continuity of activities, but It was motivated by cost reduction announced. Furthermore, it was not a run and monitored process in view of the latent needs of digital and social inclusion in the participatory governance of this council. The public really involved with social participation, mainly civil society and partners, was the crucial one, in an innovative and engaged network action, to try to make up for the verified absences and needs.